2009
DOI: 10.1007/s00702-009-0268-z
|View full text |Cite
|
Sign up to set email alerts
|

sPhospholipase A2 is inhibited by anthocyanidins

Abstract: Epidemiological studies suggest that nutritional antioxidants may reduce the incidence of neurodegenerative disorders and age-related cognitive decline. Specifically, protection against oxidative stress and inflammation has served as a rationale for promoting diets rich in vegetables and fruits. The present study addresses secretory phospholipase A(2) (sPLA(2)) as a novel candidate effector of neuroprotection conferred by anthocyanins and anthocyanidins. Using a photometric assay, 15 compounds were screened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…In this regard, STZ‐diabetic rats exhibit increased phospholipase A2 activity (Rhee et al ., ) and this change in the hippocampus may lead to some cognitive deficits and inhibition of such enzymes could diminish neurotoxicity and memory impairment (Sanchez‐Mejia et al ., ). Anthocyanidins like cyanidin can inhibit such enzymes (Dreiseitel et al ., ) and in this way we have had an improvement in performance of diabetic rats in the Y‐maze task. In addition, it has also been reported that diabetes via the hypothalamic–pituitary–adrenal axis and its related steroid corticosterone can also cause cognitive dysfunction and derangements in hippocampus‐dependent memory, perforant path synaptic plasticity and adult neurogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…In this regard, STZ‐diabetic rats exhibit increased phospholipase A2 activity (Rhee et al ., ) and this change in the hippocampus may lead to some cognitive deficits and inhibition of such enzymes could diminish neurotoxicity and memory impairment (Sanchez‐Mejia et al ., ). Anthocyanidins like cyanidin can inhibit such enzymes (Dreiseitel et al ., ) and in this way we have had an improvement in performance of diabetic rats in the Y‐maze task. In addition, it has also been reported that diabetes via the hypothalamic–pituitary–adrenal axis and its related steroid corticosterone can also cause cognitive dysfunction and derangements in hippocampus‐dependent memory, perforant path synaptic plasticity and adult neurogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…Accordingly, one of the mechanisms by which polyphenols can modulate the immune response is via direct inhibition of these proinflammatory enzymes [70]. Considering PLA 2 as the first enzyme in the AA cascade, it has been evidenced the inhibitory capabilities by polyphenols such as quercetin, kaempferol, and galangin, as well as some anthocyanidins (cyanidin, delphinidin malvidin, peonidin and petunidin) [71][72][73] Catechol (1,2-dihydroxybenzen) binds to PLA2 preventing the substrate from entering into the active site [74]. Furthermore, resveratrol and p-coumaric acid interact directly with catalytic residues of PLA2, blocking its catalytic activity [75].…”
Section: Arachidonic Acid Dependent Pathwaymentioning
confidence: 99%
“…Besides reactive oxygen species (ROS), ATs also inhibit the production of reactive nitrogen species (RNS), particularly nitric oxide (NO), as well as their associated oxidative processes [ 58 ]. Furthermore, release of pro-inflammatory mediators and adhesion molecules is suppressed by ATs via targeting of the respective signaling pathways, e.g., the arachidonic acid and the tumor necrosis factor (TNF)-α, nuclear factor (NF)-κB pathways [ 59 , 60 ].…”
Section: Functions Of Pomegranate Ats In Human Nutrition and Healtmentioning
confidence: 99%